The demand for M3 in the euro area - Guenter Coenen; Juan Luis Vega (European Central Bank (ECB), 1999)
In this paper, an empirically stable money demand model for M3 in the euro area is constructed. Starting with a multivariate system, three cointegrating relationships with economic content are found: (i) the spread between the long- and the short-term nominal interest rates, (ii) the long-term real interest rate, and (iii) a long-run demand for broad money M3. There is evidence that the determinants of M3 money demand are weakly exogenous with respect to the long-run parameters. Hence, following a general-to-specific modelling approach, a parsimonious conditional error-correction model for M3 money demand is derived which can be interpreted economically. For the conditional model, long-and short-run parameter stability is extensively tested and not rejected. Insights into the dynamics of money demand are gained by means of SVAR techniques exploring the impulse response functions of the cointegrated multivariate system.
Keywords: C22; C32; E41; 330; cointegration; error-correction model; euro area; impulse response analysis; Money demand